Analysis of Differentially Expressed MicroRNAs and Circulating Tumor Cells as Predictive Biomarkers of Platinum Chemoresistance in Primary Ovarian Carcinomas: A Prospective Study. (25th July 2019) - Lou, Emil; Vogel, Rachel I.; Hoostal, Spencer; Wong, Phillip; Grad, Aaron; Monu, Minnu; Łukaszewski, Tomasz; Deshpande, Jaai; Dickson, Elizabeth L.; Klein, Molly; Linden, Michael A.; Subramanian, Subbaya; et al.
Abstract: Lesson Learned : Circulating tumor cells, microRNA markers, or other biomarkers merit examination as part of correlative scientific analyses in prospective clinical trials. Background: Platinum chemotherapy resistance occurs in approximately 25% of patients with ovarian carcinoma; however, no biomarkers of ovarian carcinoma chemoresistance have been validated. We performed a prospective trial designed to identify tumor‐based predictive biomarkers of platinum resistance. Methods: Tumor specimens were collected from 29 women with newly diagnosed histopathologically proven primary ovarian carcinoma. Of these, 23 women had specimens accessible for assessment and outcome data available regarding chemosensitive versus chemoresistance status via review of the medical record. Tumor slices were stained with antibodies against two microRNAs (miRNAs 29b and 199a) differentially expressed in chemoresistant ovarian cancer cell lines. Additionally, blood samples obtained at the time of diagnosis were analyzed for the presence of circulating tumor cells (CTCs). Results: The average age of the patients was 64 years, and 82.6% had high‐grade epithelial carcinomas. The baseline median CA‐125 was 464 (range 32–2, 782). No statistically significant differences were observed in miR29b or 199a expression in platinum‐resistant/refractory versus platinum‐sensitive tumors. Furthermore, the presence of CTCs was not found to be statistically significantly predictive of eventual platinum resistance. Conclusion: Our analysis showed no differences in miR29b and 199a expression, and differences in baseline CTCs in women with newly diagnosed ovarian tumors were not statistically significant.